Nursing diagnosis “impaired walking” in elderly patients: integrative literature review - Vieira, Cristina Maria Alves Marques (2015)
The impaired walking nursing diagnosis has been included in NANDA International classification taxonomy in 1998, and this review aims to identify the defining characteristics and related factors in elderly patients in recent literature. Integrative literature review based on the following guiding question: Are there more defining characteristics and factors related to the nursing diagnosis impaired walking than those included in NANDA International classification taxonomy in elderly patients? Search conducted in 2007-2013 on international and Portuguese databases. Sample composed of 15 papers. Among the 6 defining characteristics classified at NANDA International, 3 were identified in the search results, but 13 were not included in the classification. Regarding the 14 related factors that are classified, 9 were identified in the sample and 12 were not included in the NANDA International taxonomy. This review allowed the identification of new elements not included in NANDA International Taxonomy and may contribute to the development of taxonomy and nursing knowledge.